A Study of Aplastic Anemia at the Department of Child Health, School of Medicine University of North Sumatera/Dr. Pirngadi Hospital, Medan - Ajuar Arif; Adi Sutjipto (Paediatrica Indonesiana, 1991)
A study of aplastic anemia in children in a period of June 1980 to June 1989 was done to evaluate the pattern of aplastic anemia in children. The cases consisted of 55 children, 30 males (54.55%) and 25 females (45.45%). Most of the patients (47.27%) were found in the age group of 10 to 15 years. The complaints were paleness (90.91%), fever (56.45%) and bleeding (52. 71%). The hemoglobin concentration was 4.25 Â± 1.17 g/dl (mean Â± SD), and the thrombocytopenia was generally severe. Prednisone or combination of prednisone and oxymethalone was given in addition to blood transfusions, antibiotics and vitamins. The outcome was difficult to evaluate because of the irregularity of treatments. Of the 55 children, 9 (18.02%) contracted leukemia after 1 - 5 months.